Glycolipid α-C-galactosylceramide is a distinct inducer of dendritic cell function during innate and adaptive immune responses of mice - Fujii, Shin-ichiro (National Academy of Sciences, 2006)
α-Galactosylceramide (α-GalCer) is the prototype compound for studying the presentation of glycolipids on CD1d molecules to natural killer T (NKT) lymphocytes. A single i.v. dose of glycolipid triggers a cascade of events involving the production of several cytokines over the course of a day, a short-lived activation of NKT and natural killer (NK) cells, and a more prolonged adaptive T cell immune response if certain antigens are given together with α-GalCer. We find that a recently described analogue, α-C-galactosylceramide (α-C-GalCer), more potently induces these innate and adaptive immune responses in mice. α-C-GalCer acts as a more effective trigger for IL-12 and IFN-γ production, although it minimally elicits IL-4 and TNF-α release into the serum. Also, α-C-GalCer better mobilizes NKT and natural killer cells to resist B16 melanoma. To help understand these effects, we find that α-C-GalCer binds more stably to dendritic cells than α-GalCer and that dendritic cells loaded with α-C-GalCer induce larger and more long lasting NKT cell responses in vivo. When glycolipid is targeted to dendritic cells in spleen together with antigens in dying cells, such as irradiated tumor cells, α-C-GalCer is active as an adjuvant for T cell-mediated immunity at lower doses, just 20 ng per mouse, where it is also able to up-regulate the required CD40L costimulatory molecule on NKT cells. Therefore, α-C-GalCer represents a glycolipid that binds more stably to dendritic cells and acts as a more effective link between innate and adaptive immunity in vivo.